Pengembangan Media Pembelajaran Aplikasi ICARUS Untuk Mendukung Pembelajaran Matematika Di SDN 81 Kota Bengukulu - Firmansyah, Suandi; Supriatna, Irfan; Amaliyah, Yuli (Universitas Bengkulu, 2026)
This research aims to develop a learning media in the form of the ICARUS (Interactive Creative Active Relevant Understanding Shape) application for plane geometry material as an effort to support mathematics learning for fourth-grade students at State Elementary School 81 Bengkulu City. This research is a Research and Development (R&D) study using the ADDIE development model. The research was conducted in 5 stages: analysis, design, development, implementation, and evaluation, carried out through small-scale trials to measure teacher and student responses. The instruments used were product validation sheets, teacher response questionnaires, and student response questionnaires. The feasibility of the ICARUS application was obtained through validation results conducted by four competent expert validators, including material experts, language experts, and graphic design experts. The validity of the ICARUS application learning media was obtained based on Aiken's V calculation results with an average material validity value of 0.96, language 0.86, and graphic design 0.93, all of which fall into the